PENERAPAN PEMBELAJARAN AKTIF TIPE BELAJAR BERAWAL DARI PERTANYAAN TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 27 PADANG - Sandra, Roji; Rismen, Sefna; Lovia, Lita (STKIP PGRI Sumbar, 2013)
The research is based on by less unusually students discuss and construct knowledge received during the learning process, and students low of comprehension of mathematical concept. The research aims to determine students comprehension of mathematical concept by applying strategy aktif learning start a question better than the students comprehension of mathematical concepts with conventional teaching in class VIII SMP 27 Padang. This type of research is experimental research on the subject with a random design. The population is class VIII SMP 27 Padang. academic year 2012/2013. Class selected sample is VIII.2 class as the experimental class and the control class VIII.4 class. The research instrument was the final test in the form of essay test reliability is 0.6947. Hypothesis testing using one side of t-test. Based on the analysis of data obtained thitung=1,93 is less than ttable=1,67, so it can be concluded that the students comprehension of mathematical concept that apply strategy aktif learning start a question is better than students comprehension of mathematical concept that apply conventional learning model in class VIII SMP 27 Padang.